Preparation of hydrophilic MgAl type layered double hydroxide films with elevated Mg/Al molar ratio on aluminum substrates via a facile approach - Satoru Fukugaichi; Yuta Tomosugi; Hiromichi Aono (Discover Materials, 2024)
Abstract A straightforward method is necessary for synthesizing hydrophilic films on aluminum fins and heat sinks intended for water vaporization-based cooling applications. Herein, a facile synthesis approach is presented for generating hydrophilic films of MgAl type layered double hydroxides (LDH) at temperatures of 20 and 50 °C, with a synthesis duration of less than 120 min. The synthesized films were comprehensively characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy, scanning electron microscopy-energy dispersive X-ray spectroscopy, and field emission scanning electron microscopy. The film hydrophilicity was assessed through contact angle (CA) measurements with water. XRD analysis revealed a higher intensity of LDH film peaks at 50 °C than at 20 °C. Additionally, the Mg/Al and Cl/Al ratios within the films increased with increasing concentrations of MgCl2. Notably, chloride anions constituted approximately 70–80% of the anions in the LDH films, with the remaining 20–30% expected to be CO3 2−. The surface morphology of the films displayed net-like and porous flower-like structures, which varied based on the synthesis conditions. The hydrophilicity of the LDH films was found to be more strongly influenced by the Mg/Al molar ratio than by the surface morphology. Particularly, the CA test indicated a hydrophilicity threshold at a Mg/Al molar ratio of approximately 2.0, with a CA of 0° when the molar ratio exceeded 2. The resultant hydrophilic film on aluminum is potentially applicable to vaporization-type coolers.